2014
DOI: 10.1108/ebr-04-2013-0080
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and environmental reporting in controversial industries

Abstract: Purpose-Over the last few decades, corporate social responsibility (CSR) has received a large amount of attention in research and in practice. As a response to the growing awareness of and concern about social and environmental issues, an increasing number of companies are proactively publishing their CSR-related principles and activities. The overall research question of this study is derived from legitimacy theory and is aimed at elucidating the relationship between industry sector and CSR communication. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 84 publications
(92 reference statements)
3
78
1
5
Order By: Relevance
“…An example of corporate social responsibility for marine conservation would be a large retailer buying and selling sustainably-harvested seafood using the Marine Stewardship Council scheme (Gulbrandsen, 2009). Despite evidence of 'green washing' whereby companies market themselves as environmentally responsible without changing practices to minimise negative impacts, there are many examples of corporate social responsibility reducing environmental impacts (McWilliams et al, 2006;Dahl, 2010;Wan and Walker, 2012;Nalband and Al-Amri, 2013;Pomering et al, 2013;Reider-Gordon et al, 2013;Kilian and Hennigs, 2014;Lam, 2014). Another type of business sits at this place of the spectrum: businesses that pass the 'negative screening' requirements of the growing number of 'socially-responsible investment' funds because they have 'less bad' social and environmental practices (Lydenberg and Grace, 2014).…”
Section: Environmental Damages and Externalitiesmentioning
confidence: 97%
“…An example of corporate social responsibility for marine conservation would be a large retailer buying and selling sustainably-harvested seafood using the Marine Stewardship Council scheme (Gulbrandsen, 2009). Despite evidence of 'green washing' whereby companies market themselves as environmentally responsible without changing practices to minimise negative impacts, there are many examples of corporate social responsibility reducing environmental impacts (McWilliams et al, 2006;Dahl, 2010;Wan and Walker, 2012;Nalband and Al-Amri, 2013;Pomering et al, 2013;Reider-Gordon et al, 2013;Kilian and Hennigs, 2014;Lam, 2014). Another type of business sits at this place of the spectrum: businesses that pass the 'negative screening' requirements of the growing number of 'socially-responsible investment' funds because they have 'less bad' social and environmental practices (Lydenberg and Grace, 2014).…”
Section: Environmental Damages and Externalitiesmentioning
confidence: 97%
“…For example, from a finance lens, Jo and Na () show that stakeholders in CIs may perceive CSR as unethical, which could backlash and increase firm risk. Accounting research has reported that stakeholders in these sectors have greater informational needs, making companies more prone to disclose CSR reports (Grougiou et al, ; Kilian & Hennigs, ). Cai et al () argue that better social performance increases firm value, but Rodrigo, Duran, and Arenas () hint otherwise because stakeholders differ due to market‐level (business‐to‐business or business‐to‐consumer) or institutional factors (developed or emerging nation).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In controversial contexts, Grougiou et al (), Kilian and Hennigs (), and Toppinen and Korhonen‐Kurki () conceptually suggest that these companies are more prone to publish CSR reports to gain a reputational edge. This insight is essential, as legitimacy theory has been one of the main frameworks to explain non‐financial disclosure: these documents are an explicit CSR‐related activity in response to information‐seeking stakeholders, so that these parties can certify that the entity's actions are proper in terms of societal expectations, norms, values, and so on (Cho, Michelon, Patten, & Roberts, ; Deegan, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Business corporations carry out sustainability/social responsibility/citizenship practices for various motives: value-driven motives (connected to corporate culture), stakeholder-driven motives (responsiveness to stakeholders' claims and expectations) and performance-driven motives (increasing financial performance) (Kilian and Hennigs 2014). However, safeguarding corporate image/reputation and avoiding environmental disasters are certainly very important motives (Özçelik et al 2015).…”
Section: Introductionmentioning
confidence: 99%